Innovation in Learning Economic Law of Sharia through the Independent Community Service Approach at SD IT Muslimat 1 Tarakan, North Kalimantan - Nur Aisyah; Muhamad Qustulani (International Journal of Management and Business, 2025)
Learning Islamic economic law in elementary schools requires innovative steps to bridge students' understanding of abstract concepts derived from religious values ​​and economic principles. The purpose of this article is to explain the method of learning innovation in Islamic economic law through the independent KKM approach at SD IT Muslimat 1 Tarakan, along with the impact of the activities and the obstacles encountered. The benefit of this article is as an academic paper that serves as a guideline in learning innovation in Islamic economic law. This research activity uses a direct class teaching method that allows direct interaction between facilitators, teachers, and students in an active and participatory classroom atmosphere. The results of the study indicate that the learning innovation in Islamic economic law through the independent KKM approach at SD IT Muslimat 1 Tarakan is able to have an impact on students to practice forming Islamic character, independence, skills, learning motivation, financial literacy, and encourage continuous innovation in learning Islamic economic law. However, a concrete solution is needed, namely the formation of a curriculum for learning Islamic economic law so that learning innovation can be sustainable.